Using Mixed Data Sampling (MIDAS) To Study The Impact Exchange Rate Volatility On Consumer Prices In Syria During The Period 2011-2019 (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to study the method of using MIDAS regression models in the econometric,  By stating the problem addressed by these models, These models are characterized by the possibility of interpreting a variable measured at a frequency (annual - quarterly) as a function of the current and previous values ​​of a variable measured at a higher frequency (monthly - weekly), To obtain more accurate results in the study of impact, nowcasting and forecasting by taking advantage of the full information content of high frequency data. And to understand the mechanism of using MIDAS regression models, The effect was studied Exchange rate volatility Which is measured quarterly monthly on the consumer price index, which is measured frequency monthly And the use of the estimated model for forecasting consumer prices based on data from the Central Bank of Syria and the Central Bureau of Statistics in Syria during the period 2011-2019. يهدف هذا البحث إلى بيان آلية وأهمية استخدام نماذج الانحدار ذات الترددات الزمنية المختلفة MIDAS، وذلك من خلال بيان المشكلة التي عالجتها هذه النماذج عن سابقتها، حيث تمتاز هذه النماذج بإمكانية تفسير متغير يتم قياسه عند تردد ما (سنوي – فصلي) كدالة للقيم الحالية والسابقة لمتغير يتم قياسه بتردد أعلى (شهري – اسبوعي)، وذلك للحصول على نتائج أكثر دقة في دراسة التأثير والتنبؤ الآني والتوقع من خلال الاستفادة من كامل المحتوى المعلوماتي للبيانات ذات التردد المرتفع. ولتوضيح آلية استخدام نماذج الانحدار MIDAS، تمّت دراسة تأثير تقلبات متغير سعر الصرف الذي يتم قياس تردده بشكل ربع شهري على متغير أسعار المستهلك والذي يتم قياس تردده بشكل شهري، واستخدام النموذج المقدر للتنبؤ بأسعار المستهلك وذلك بالاعتماد على بيانات مصرف سورية المركزي والمكتب المركزي للإحصاء في سورية خلال الفترة الممتدة 2011 – 2019.